PERAN KEPOLISIAN DALAM PENEGAKAN HUKUM TINDAK PIDANA ANAK YANG MEMAKAI NARKOBA (STUDI KASUS DI WILAYAH HUKUM POLRES NGAWI) - Kusuma, Redho Rachmad Hadi; Hartoyo, Hartoyo; Nasoetion, Dedi Wardana (Gapenas Publisher, 2025)
This study examines the role of Ngawi Resort Police (Polres Ngawi) in law enforcement concerning children involved in drug abuse and trafficking. Children are a vital asset for national development and require special protection from threats such as narcotics. The issue of narcotics abuse now transcends age boundaries, with children often targeted due to their impressionable curiosity. Key legal frameworks include Indonesian Law No. 11 of 2012 on the Juvenile Criminal Justice System and Indonesian Law No. 35 of 2014, an amendment to Law No. 23 of 2002, concerning Child Protection. This research aims to analyze the preventive and preemptive efforts, as well as the application of diversion, restorative justice, and rehabilitation implemented by Polres Ngawi. The findings indicate that Polres Ngawi employs legal education in schools and community-based early detection as primary preventive and preemptive measures. In handling child offenders, Polres Ngawi prioritizes diversion, restorative justice, and rehabilitation to avoid formal judicial processes and facilitate comprehensive recovery. Recommendations include strengthening cross-sectoral coordination, enhancing human resource capacity for facilitators, educating communities on alternative child handling approaches, optimizing access to rehabilitation facilities, empowering local community actors, and continuously evaluating ongoing programs